Arrowheads and spear points in the prehistoric Southeast : a guide to understanding cultural artifacts - Culberson, Linda Crawford, 1953- (University Press of Mississippi, 1993)
The Native American tribes of what is now the Southeastern United States left intriguing relics of their ancient cultural life. Arrowheads, spearpoints, stone tools, and other artifacts are found in newly plowed fields, on hillsides after a fresh rain, or in washed-out creekbeds. These are tangible clues to the anthropology of the Paleo-Indians, and the highly developed Mississippian peoples. This indispensable guide to identifying and understanding such finds is for conscientious amateur archeologists who make their discoveries in surface terrain. Many are eager to understand the culture tha.